Tcl/tk a developer's guide - Flynt, Clif. (San Francisco, Calif. : Morgan Kaufmann ; Oxford : Elsevier Science, 2003)
Tcl/Tk (Tool Command Language/Tool Kit) makes it fast and easy to implement any type of application, from games to network analyzers. Tcl/Tk is a full-bodied, mature programming platform used by NASA rocket scientists, Wall Street database experts, Internet designers, and open source programmers around the world. Tcl/Tk's multi-faceted and extensible nature make it ideal for developing end-user GUIs, client/server middleware, Web applications, and more. You can code completely in Tcl, use any of hundreds of extensions, call C or Java subroutines from Tcl/Tk, or use Tcl to glue legacy applications together. Written from a programmer's perspective, Tcl/Tk: A Developer's Guide describes how to use Tcl's standard tools and the unique features that make Tcl/Tk powerful: including graphics widgets, packages, namespaces, and extensions. With this book an experienced programmer will be able to code Tcl in a few hours. In just a few chapters you will learn about Tcl features that allow you to isolate and protect your code from being damaged in large applications. You will even learn how to extend the language itself. Tcl/Tk: A Developer's Guide clearly discusses development tools, proven techniques, and existing extensions. It shows how to use Tcl/Tk effectively and provides many code examples. This fully revised new edition is the complete resource for computer professionals, from systems administrators to programmers. It covers versions 7.4 to 8.4 and includes a CD-ROM containing the interpreters, libraries, and tutorials to get you started quickly. Additional materials in the book include case studies and discussions of techniques for the advanced user. On the CD-ROM *Distributions for Tcl 8.3 and 8.4 for Linux, Solaris, Macintosh, and Windows. *A copy of ActiveTcl from ActiveState. *The latest release of TclTutor. *How-to's and tutorials as well as copies of all the tools discussed in the book. *The author's "Tclsh Spot" articles from :login; magazine and the "Real World" Tcl/Tk chapters from the first edition. *Demo copies of commercial development tools from ActiveState and NeatWare. *Many open source Tcl/Tk development tools. *Tcl/Tk design guidelines. *Brings beginners up to speed quickly. *Overview of Tcl development tools, popular extensions, and packages. *Tips, style guidelines, and debugging techniques for the advanced user.
Tcl/Tk Features; The Mechanics of Using the Tcl and Tk Interpreters; Introduction to the Tcl Language; File System; Disk I/O and Sockets; Using Strings and Lists; Building Complex Data Structures with Lists and Arrays; Procedure Techniques; Namespaces and Pack; Introduction to Tk Graphics; Using the Canvas Widget; The Text Widget and htmllib; Tk Megawidgets; Writing a Tcl Extension; Extensions and Package; Programming Tools; Tips and Techniques.
Includes indexes.
Includes bibliographical references (pages xxx-xxxi) and index.
Keywords: Tcl (Computer program language); Tk toolkit; Computer programming; Electronic books